2021
DOI: 10.1042/bcj20210200
|View full text |Cite
|
Sign up to set email alerts
|

Identifying SARS-CoV-2 antiviral compounds by screening for small molecule inhibitors of nsp12/7/8 RNA-dependent RNA polymerase

Abstract: The coronavirus disease 2019 (COVID-19) global pandemic has turned into the largest public health and economic crisis in recent history impacting virtually all sectors of society. There is a need for effective therapeutics to battle the ongoing pandemic. Repurposing existing drugs with known pharmacological safety profiles is a fast and cost-effective approach to identify novel treatments. The COVID-19 etiologic agent is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a single-stranded positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…We next used this assay to determine the effect of substrate concentration on initial reaction velocities. We found that, in contrast with all of the other enzymes we have examined in this series of papers [31][32][33][34][35][36], reaction rates did not plateau at higher substrate concentrations but instead continued to increase non-linearly, indicating that nsp15 endoribonuclease behaves as an allosteric enzyme towards the 6 nt U substrate, with a K half of 2140 nM (Figure 3A and Supplementary Figure S2A).…”
Section: Fluorescent Biochemical Kinetic Screen For Sars-cov-2 Nsp15 Inhibitorsmentioning
confidence: 76%
See 2 more Smart Citations
“…We next used this assay to determine the effect of substrate concentration on initial reaction velocities. We found that, in contrast with all of the other enzymes we have examined in this series of papers [31][32][33][34][35][36], reaction rates did not plateau at higher substrate concentrations but instead continued to increase non-linearly, indicating that nsp15 endoribonuclease behaves as an allosteric enzyme towards the 6 nt U substrate, with a K half of 2140 nM (Figure 3A and Supplementary Figure S2A).…”
Section: Fluorescent Biochemical Kinetic Screen For Sars-cov-2 Nsp15 Inhibitorsmentioning
confidence: 76%
“…Reaction slopes in the presence of each compound were calculated and normalised to the DMSO-containing positive controls (control reactions) on each plate (Figure 3C and Supplementary Figure S2B). We did not find any inhibitors that showed residual activities <0.7 in both concentrations (Figure 3D), which was surprising given the results of similar screens from our accompanying manuscripts [31][32][33][34][35][36][37]. Therefore, we considered compounds that had residual activities <0.9 and had a Z-score <−4 (Figure 3E and Supplementary Figure S2D).…”
Section: Fluorescent Biochemical Kinetic Screen For Sars-cov-2 Nsp15 Inhibitorsmentioning
confidence: 85%
See 1 more Smart Citation
“…Compounds that inhibited viral replication without deleterious effects on uninfected cells were selected as candidate antivirals. The seven papers describing these results are published in this addition of the Biochemical Journal [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…While all inhibited viral replication and had synergistic interactions with remdesivir the severe side effects associated with Trifluperidol may limit its use as a single agent. A series of compounds related to suramin were shown to inhibit the RdRp encoded by nsp12 in complex with its processivity factors nsps 7 and 8 [3]. Suramin was developed over 100 years ago by Bayer for the treatment of river blindness and sleeping sickness and is known to inhibit multiple viruses.…”
mentioning
confidence: 99%